Pengaruh Media Visual terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Kelas V SD Negeri 174552 Tambunan Kecamatan Balige Kabupaten Toba Tahun Pelajaran 2023/2024 - Ayu Gandari Sipayung; Sandy Ariawan; Grecetinovitria Butarbutar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Based on the observation, a problem was found regarding the lack of interest in learning Christian Religious Education and Character Education in class V of SD Negeri 174552 Tambunan. This is due to the difficulty of students in understanding the learning material. This study aims to determine the effectiveness of learning using visual media compared to learning using conventional media. The type of experimental research used is Quasi Experiment. Class V-A is the experimental class and class V-B is the control class. The dependent variable in this study is the interest in learning Christian Religious Education and Character Education and the independent variable is visual media. The data collection technique used a questionnaire. The results of the study used data from the initial test scores (Pretest) and the final test (Posttest). The results of the study showed that the use of visual media in the experimental class was more effective than the use of conventional learning media in the control class. The results of the t-test in the experimental class showed tcount (7.74) > ttable (2.01) H0 was rejected. The results of the t-test in the control class showed tcount (0.52) < ttable (2.01) H0 was accepted. Then N-Gain obtained the average N-Gain in the experimental class 0.37, in the control class the average N-Gain 0.03. The results of the N-Gain t-test of the experimental and control classes showed t count (10.29) > t table (2.01) H0 was rejected. The conclusion of this study is that learning using visual media is more effective than learning using conventional media.